Profili del sacro all'interno dei sistemi giuridici c.d. “plurali”. Recenti tendenze nell'ordinamento costituzionale canadese (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Premessa - 2. La tutela del sentimento religioso in Canada: un inquadramento costituzionale - 3. Il reato di Hate Speech - 4. Il reato di blasfemia - 5. Considerazioni conclusive.Legal features of the sacred in pluralist systems. Recent developments in the Canadian constitutional legal orderABSTRACT: Nowadays the concept of "sacred" is characterised by a pluralization of the religious phenomena, which are barely defined from a legal point of view by the State. One of the criticalities of this scenario lies in the fact that there is no uniqueness on the limits that the State determines in outlining the boundaries of a religion. The risk of this lack of precise limits could be, inter alia, the offense to religious sentiment. The Author investigates the legal provisions that limit offences to religious sentiment such as the crime of hate speech and blasphemy in Canada. The latter is in fact a pluralist system considered as a good example for other States.